Biocharcoal Dari Kulit Kakao (Theobroma cacao L)Untuk Mengadsorpsi Ion Logam Timbal Pb - Podala, Katherina; Walanda, Daud K.; Napitupulu, Mery (Jurnal Akademika Kimia, 2015)
Cacao is a commodity crop growth in the plantation farmers, particularly in Central Sulawesi. Processed of the cocoa fruits are mainly as the food products. Furthermore, the cocoa bark just become rubbish. This study aims to utilize the waste of cocoa bark to be used as biocharcoal to adsorb lead metal ions. The method used was spectrophotometry, where the lead ions concentration absorbed was measured using a Spectrodirect spectrophotometer. The results showed that at the optimum contact time 90 minutes, the lead ion capacity adsorption was 97% and the lead weight adsorbed was 25.26 mg/g. The optimum weight of 60 mg, where the lead ions capacity adsorption was 96.88% and the lead weight adsorbed was 25.22 mg/g. The optimum adsorption capacity was 40 ppm, where the lead ions adsorption obtained was 99.61% and the lead weight adsorbed was 10.84 mg/g.